Circadian clock of two insect model species - Drosophila melanogaster and Tribolium castaneum - Fexová, Silvie (Jihočeská univerzita, 2010)
The aim of this study was to determine the specific interactions among clock gene alleles in Drosophila melanogaster and their effect on the function of the circadian clock. The second part of this study deals with the expression pattern (both temporal and spatial) of two core clock factors known from Drosophila, period and timeless, in the central nervous system of the red flour beetle, Tribolium castaneum.
Circadian clock of two insect model species - Drosophila melanogaster and Tribolium castaneum
Keywords: circadian clock; Drosophila; Tribolium; circadian clock; Drosophila; Tribolium